Apical localization of PMCA2w/b is enhanced in terminally polarized MDCK cells - Antalffy, Géza (2011)
The “w” splice forms of PMCA2 localize to distinct membrane compartments such as the apical membrane of the lactating mammary epithelium, the stereocilia of inner ear hair cells or the post-synaptic density of hippocampal neurons. Previous studies indicated that PMCA2w/b was not fully targeted to the apical domain of MDCK cells but distributed more evenly to the lateral and apical membrane compartments. Overexpression of the apical scaffold protein NHERF2, however, greatly increased the amount of the pump in the apical membrane of these epithelial cells. We generated a stable MDCK cell line expressing non-tagged, full-length PMCA2w/b to further study the localization and function of this protein. Here we demonstrate that PMCA2w/b is highly active and shows enhanced apical localization in terminally polarized MDCK cells grown on semi-permeable filters. Reversible surface biotinylation combined with confocal microscopy of fully polarized cells show that the pump is stabilized in the apical membrane via the apical membrane cytoskeleton with the help of endogenous NHERF2 and ezrin. Disruption of the actin cytoskeleton removed the pump from the apical actin patches without provoking its internalization. Our data suggest that full polarization is a prerequisite for proper positioning of the PMCA2w variants in the apical membrane domain of polarized cells.